Pengaruh Pendapatan Asli Daerah, Kemandirian Keuangan Daerah, Belanja Modal dan Total Aset Terhadap Tingkat Pengungkapan Wajib LKPD Provinsi di Pulau Sumatera - Fitri Khairunnisa; Zulkifli; Riana Mayasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the factors influencing the level of transparency required in local government financial reports on Sumatra Island until 2023. The following are the research factors: the amount of required LKPD disclosure, PAD, capital expenditure, total assets, and regional financial independence. Saturated sampling was used in this quantitative research design to select ten provinces. Data were sourced from local government financial documents. The results show that the level of required LKPD disclosure is substantially influenced by total assets, negatively and significantly by capital expenditure, and positively and significantly influenced by regional financial independence, but partially unaffected by the independent variable, PAD. However, the amount of required LKPD disclosure is also influenced by independent factors. The impact of independent factors in previous studies is shown in the literature review, which supports this.